FDTD Application of Targets Electromagnetic Scattering in Layered Space - Jiang Yan-nan; Zhu Si-xin; Wang Bin; Yu Xin-hua (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Finite Difference Time Domain (FDTD) was used to characterize the electromagnetic scattering (EMS) for targets in layered space. A new set of 1D modified Maxwell equations and auxiliary equations with incident angle was derived from 2D Maxwell equations and was used to compute the electromagnetic field in vertical boundary in 2D total field-scattered field (TF/SF), and thus incidence of uniform plane wave in time domain can be directly realized. In order to avoid complex Somerfield integration, the reciprocity theorem was used to simplify an extrapolation algorithm. Then the proposed algorithm and program in this paper were validated by applying them to compute the electromagnetic scattered field for targets in half-space and the radiation field for line current in layered lossy space. Finally this algorithm was used to characterize EMS for a tunnel in multi-layered space, for a tunnel open to vehicle, and for a tunnel and vehicle in lossless layered space. The results show the vehicle has a great impact on the scattering field, and the layered media surrounded the target can shield the scattering field. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3699